Dig deep into Rolls-Royce´s true value - Kong, Ruiqi (2022)
This paper introduces the development process of Rolls-Royce in the aerospace and power industry and an overview of the company's revenue in recent years. In the second part, it introduces the share holder structure and their impact on the valuation model in detail. In the last part of the forecast, the value drivers and the forecast of future income are described in detail, and the value, cogs and expenses of there structuring part are analyzed. In addition, the dividends of the company are analyzed. Finally, the valuation process and results under DCF method and Multiple method are explained in detail, so as to evaluate the value of the company.